Financial banking performance of ASEAN-5 countries in the digital era - Nazaruddin Malik; Arlini Oktavia; Muhammad Sri Wahyudi Suliswanto; Firdha Aksari Anindyntha (Jurnal Keuangan dan Perbankan, 2020)
The improvement of technology and information create a digital era in all aspects of the economy, one example is in the banking sector. This study aims to find out and compare the financial performance of banking industry in Indonesia, Singapore, Malaysia, Thailand and the Philippines in the period 2012-2017. The model used in hypothesis testing using one way ANOVA parametric test. Furthermore, using the panel regression analysis and results from coefficient of determination (R2) from the regression to see the influence of digital era on ASEAN banking financial performance. The results of the study showed that the financial performance of ASEAN-5 banks differ significantly with other ASEAN countries and the average value of Indonesian banking financial performance showed better results than the other four ASEAN countries on CAR, ROA, and NIM ratios. However, on average the LDR ratio shows that Singapore, Malaysia and Thailand are better than Indonesia. There are two of five variables that have a significant effect on bank profitability, namely the implementation of digital banking and the funding variables from third parties in banks. Other variables that are not significant are completeness in information of digital banking provided by the bank, the number of internet banking users of each bank, and the amount of credit channeled by the bank. The coefficient of determination (R2) is 41%, which means the effect of using digital banking is good enough on financial performance of bank in ASEAN.JEL Classification: G21, G32 How to Cite:Malik, N., Oktavia, A., Suliswanto, M. S. W., Anindyntha, F. A. (2020). Financial banking performance of ASEAN-5 countries in the digital era. Jurnal Keuangan dan Perbankan, 24(1), 117-130.DOI: https://doi.org/10.26905/jkdp.v24i1.2641